Uprooting the Pretexts of gender-disparity and its aftermaths in Mary E. Wilkins Freeman’s The Revolt of Mother - Malesela Edward Montle (Journal of English Language Studies, 2023)
The global arena in the present-day is plagued by gender-related issues such as toxic masculinity, misogyny and patriarchy. These problems are so menacing to an extent that various mechanisms such as campaigns, media platforms and governmental interventions are besought to combat them. These stratagems have tackled gender-related ills head-on with an intense focus on their impact on societies. Therefore, the paper aims to revisit the genesis of gender-disparity and its development into a pandemic in an effort to uproot its pretexts. There is no adequate scholarly exploration to trace the foundations of gender-disparity and the study pinpoints this as a gap in the on-going discourse on gender issues. The paper employed a qualitative methodology to fulfil its main objective alluded to above and has relied on literary appreciation as a case in point. This noted, The Revolt of Mother by Mary E. Wilkins Freeman has been textually analysed due to its Germanness to the study. The paper’s findings delineate that gender-disparity is rooted in traditional and religious underpinnings that are abused to perpetrate discriminatory attitudes against women. These findings will aid and make a significant contribution to global contest against gender-related ills by tracing gender-disparity from its genesis and unmasking its janitors, thus, addressing the gap and providing additional insights to the existing body of knowledge on the identified problem.